A crisis of global sustainability - Kanninen, Tapi (Abingdon, Oxon New York Routledge, 2013)
"The book provides a critical history of the concept of sustainability and the various institutional measures taken to promote, implement and enforce sustainable development"--Provided by publisher.
Keywords: Club of Rome; Sustainable development -- Government policy; Sustainable development